2002
DOI: 10.1038/sj.leu.2402434
|View full text |Cite
|
Sign up to set email alerts
|

The coexpression of the apoptosis-related genes bcl-2 and wt1 in predicting survival in adult acute myeloid leukemia

Abstract: The Wilms tumor gene wt1 and the protooncogene bcl-2 are upregulated in acute myeloid leukemia (AML) and are known to regulate or to inhibit the onset of apoptosis. Since wt1 has been shown to regulate the expression of bcl-2, we investigated the association of the expression of these genes and their prognostic relevance in AML. Leukemic blasts from the bone marrow of 152 patients with newly diagnosed AML were analyzed for bcl-2 and wt1 mRNA expression using RT-PCR and quantitative PCR. Therapy outcome was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 37 publications
(41 reference statements)
5
45
0
Order By: Relevance
“…In this regard, the WT1 gene has been shown to repress the expression of the pro-apoptotic gene Bak 40 and to upregulate the antiapoptotic genes Bcl-2 (ref. 41) and A1/BFL1 (ref. 42) in myeloid lineage cells.…”
Section: Criterion 3: Oncogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the WT1 gene has been shown to repress the expression of the pro-apoptotic gene Bak 40 and to upregulate the antiapoptotic genes Bcl-2 (ref. 41) and A1/BFL1 (ref. 42) in myeloid lineage cells.…”
Section: Criterion 3: Oncogenicitymentioning
confidence: 99%
“…These studies, including WT1 peptide and WT1-targeted dendritic cell vaccine trials, have unequivocally established that CD8 þ T-cell immune responses specific to WT1 can be induced by active immunization in a substantial number of AML patients. 14 In those patients, multiple WT1 CTL epitopes have been recognized as immunogenic (including WT1 [37][38][39][40][41][42][43][44][45] , WT1 [126][127][128][129][130][131][132][133][134] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ), demonstrating the excellent in vivo immunostimulatory potential of WT1 (Table 1). 14,72 This is further supported by the capacity to induce WT1-specific CD4 þ helper T-cell immunity in patients with AML through active immunization.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of WT1 in breast cancer has both prognostic and biological effects. Several groups have found that high levels of WT1 expression in breast cancer are associated with a worse prognosis (7)(8)(9). This is possibly due to a proliferation and survival effect provided by WT1 because down-regulation of WT1 inhibits breast cancer growth (10).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown elevated WT1 expression in diverse cancer types, including leukemia (34-37), breast (38)(39)(40), Ewing sarcoma (41), ovarian (42), mesothelioma, and pulmonary adenocarcinomas (43). Additionally, WT1 is being investigated as a potential prognostic marker for both leukemia and breast cancer (39,44).…”
Section: Wt1 Expression In Non-wilms Cancermentioning
confidence: 99%